2018
DOI: 10.1016/j.ebiom.2018.07.026
|View full text |Cite
|
Sign up to set email alerts
|

Possible Roles of Mitochondrial Dynamics and the Effects of Pharmacological Interventions in Chemoresistant Ovarian Cancer

Abstract: Ovarian cancer is the major cause of death out of all the gynecologic cancers. The prognosis of this cancer is quite poor since patients only seek treatment when it is at an advanced stage. Any early biomarkers for this cancer are still unknown. Dysregulation of mitochondrial dynamics with associated resistance to apoptosis plays a crucial role in several types of human carcinogenesis, including ovarian cancers. Previous studies showed that increased mitochondrial fission occurred in ovarian cancer cells. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 45 publications
1
37
0
Order By: Relevance
“…The balance between these opposing events, at every time or cell demand, determines organelle morphology, which acts as an intracellular signal that instructs different metabolic pathways, reflecting the different physiological functions of the cell. For instance, an elongated network sustains oxidative phosphorylation (OXPHOS) for a correct assembly of the electron transport chain (ETC) complexes, and an optimal ATP production, besides diluting the matrix content (38). A fragmented network, instead, promotes aerobic glycolysis and mitophagy or accelerates cell proliferation in response to nutrient excess and cellular dysfunction (38).…”
Section: Mitochondrial Dynamics In Memory T Cells and T Cell Migrationmentioning
confidence: 99%
“…The balance between these opposing events, at every time or cell demand, determines organelle morphology, which acts as an intracellular signal that instructs different metabolic pathways, reflecting the different physiological functions of the cell. For instance, an elongated network sustains oxidative phosphorylation (OXPHOS) for a correct assembly of the electron transport chain (ETC) complexes, and an optimal ATP production, besides diluting the matrix content (38). A fragmented network, instead, promotes aerobic glycolysis and mitophagy or accelerates cell proliferation in response to nutrient excess and cellular dysfunction (38).…”
Section: Mitochondrial Dynamics In Memory T Cells and T Cell Migrationmentioning
confidence: 99%
“…The GTPase DRP1 promotes mitochondrial fission, and high DRP1 expression is reported in several cancer types. 22,24,26,28 Reducing DRP1 activity is considered as a potential therapeutic approach for cancer. Mdivi-1 (a widely accepted DRP1 inhibitor) induced cancer cell death and decreased tumour size in xenograft models.…”
Section: Discussionmentioning
confidence: 99%
“…25 High expression of DRP1 in cancer may be a potential target for cancer treatment. 4,5,22,24,[26][27][28] Mitochondrial division inhibitor 1 (mdivi-1) is an efficacious inhibitor of mitochondrial division in yeast and was identified from a chemical screen for compounds that alter mitochondrial morphology. 29 Not surprisingly, mdivi-1 has been widely used as a mitochondrial fusion inducer.…”
mentioning
confidence: 99%
“…Mitochondrial autophagy (mitophagy) maintains mitochondria mass and function by clearing damaged or overloaded mitochondria. Kingnate et al [36] proposed that increased mitochondrial fusion and reduced mitochondrial fission may be one of the mechanisms of cisplatin resistance in ovarian cancer cells. Williams et al [37] suggested that inhibition of mitochondrial fission leads to mitophagy suppression.…”
Section: Mitophagymentioning
confidence: 99%